Result Based Manajemen Sistem untuk Monitoring dan Evaluasi Kegiatan Bimbingan Dasar Keislaman - Okfalisa, Okfalisa; Simaremare, Harris; Abdillah, Rahmad; Najwa, Nina Fadilah (JSINBIS (Jurnal Sistem Informasi Bisnis), 2019)
The Islamic values in the integrated curriculum should be reflected in governance, teaching lifestyle, and society dedication. The Islamic basic mentoring activity was the routine activity in UIN SUSKA Riau. That activity had been going on since 2010 and had unoptimization through stakeholder dissatisfaction with performance output. This research has developed a model by Result based for monitoring and evaluating the activity implementation. The results of the modeling mechanism were implemented in the construction of a Result Based Management Information System prototype. This research conducted by 7 constructs with 32 indicators that had been statistically tested by Confirmatory Factor Analysis to know the significance and the relation between indicators and constructs. This model was tested descriptive statistic to measure the activity implementation performance in accordance with the expected output. The results of performance activity at the Faculty of Science Technology were at the middle level. The construction of a prototype using Object Oriented Analysis had been successfully carried out with very good results in testing the UAT and Black Box. The system had 6 actors based on the stakeholder requirements and the system was successfully monitoring and evaluating problem and activity as long as the implementation. Performance information in graphically was to help the leader and top management for making decision and policy fixing. The discussion forum was developed as sharing information platform between the leader, the manager and the lecturer, the fellow lecturer, the lecturer and the participants. Thus, the transformation and transparency in implementation activity were formed.